An alternative and comprehensive approach to estimate trapped hydrogen in steels using electrochemical permeation tests. (16th October 2020) - Samanta, Santigopal; Kumari, Puja; Mondal, Kallol; Dutta, Monojit; Singh, Shiv Brat
Abstract: The present study critically discusses the apparent diffusivity of H during build-up and decay permeation transients in four microalloyed line-pipe steels using Devanathan-Stauchursky cell in galvanostatic-potentiostatic condition. Among the existing models, the Carvalho's solution has been found to give the best fit with the experimental build-up transient. The numerical solution of trapping and detrapping events of H during build-up transients is investigated by solving the McNabb-Foster model. The residual hydrogen was measured in the steels using LECO-DH603 hydrogen determinator after saturation H-charging. Further the Carvalho's exponent of permeation transient has been found to have good correlation with the H trapping-detrapping rates during the permeation test and also with the residual H content in the steel. Finally, empirical relationships have been proposed that can be used to estimate the residual H in the studied steels along with the trapping-detrapping parameters using the permeation test data. Graphical abstract: Image 1 Highlights: The study discusses an easy approach for estimation of trapped-H in steel. Hydrogen permeation test was carried out for four microalloyed line-pipe steels. Devanathan-Stauchursky cell ( galvanostatic-potentiostatic) was used for permeation. Numerical solution for trapping and detrapping events of H was established. Empirical relationships are proposed to estimate residual H from permeation data.